Exploring Candidates’ Response Strategies to Oral Questioning in the EFL Thesis Defenses: A Celce-Murcia’s Framework Approach - Kamlasi, Imanuel; Pratama, Hendi; Wahyuni, Sri; Bahri, Seful (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
The thesis defense examination (TDE) is a high-stakes academic interaction in which candidates must communicate effectively and persuasively to demonstrate their understanding of the subject matter. Understanding response strategies is vital to establishing effective communication within a thesis defense. This study analyzed candidates’ response strategies in the EFL thesis defenses using Celce-Murcia’s framework. The data collection involved observing eight thesis defenses and recording oral interactions, which were then transcribed for analysis. To ensure the credibility of the data analysis, an inter-coder agreement was calculated, resulting in a Cohen’s kappa value of κ = 0.82, indicating a high level of agreement between coders. The findings showed that candidates frequently employed expansion strategies when answering examiners’ questions. Confirmation strategies also appeared with relatively high frequency. Repetition and reduction and repair strategies were used with moderate frequency, whereas rephrasing and rejection were rarely employed. This study reveals that EFL candidates often add more information to their responses and confirm their answers during interaction in the thesis defenses.